ANALISIS TINGKAT RASIO LIKUIDITAS TERHADAP LAPORAN KEUANGAN PT PLN PERSERO TAHUN 2018 – 2022 - Hasanudin, Hasanudin (POLITEKNIK LP3I JAKARTA, 2023)
A company's financial statements can be evaluated by analyzing using financial ratios. The ratio itself has several groups such as liquidity, profitability and …. This study uses secondary data obtained indirectly from financial statements by using liquidity ratio measurements. Quantitative method with descriptive analysis mode is used in this study which aims to analyze economic indicators so that after analysis, the company can find out and evaluate whether the company's ratio value can meet the standard or vice versa. The results of the study show that the analysis of PT PLN Persero's financial statements for 2018 - 2022 has experienced instability. In terms of liquidity ratios, it can be shown that the status is not good in the Current Ratio method (lancer ratio) which obtains an average value in 5 years of 74.54% which is below the standard value of the current ratio and the Quick Ratio (fast ratio) which obtains an average value in the last 5 years 65.74% where both scores did not meet the criteria. Recommendations for PT PLN Persero to pay attention to financial reports by increasing their financial ratios so that they can achieve maximum weight in the following year. Keywords : Liquidity Ratio; Ratio Analysis, Financial Report